The Validity of Student Interest Instrument in Learning Arabic Using Exploratory Factor Analysis - Hidayah, Nurul; Parihin; Ahmad (Global Action and Education for Society, 2025)
This study aims to evaluate the construct validity of a student interest instrument in Arabic language learning using the Exploratory Factor Analysis (EFA) approach. The research employs a quantitative approach with data collected through a Likert-scale questionnaire distributed to fourth, fifth, and sixth-grade students at Madrasah Ibtidaiyah (MI). Validity testing was conducted using the Kaiser-Meyer-Olkin (KMO) and Bartlett’s Test to assess sample adequacy and data suitability for factor analysis. The EFA results identified three main factors: intrinsic motivation, learning relevance, and learning comfort, which explained a cumulative variance of 57.4%. The first factor contributed the most, emphasizing the importance of intrinsic motivation in shaping students' interest. Communalities values ranged from 0.340 to 0.784, indicating that most items adequately represented the extracted factors. This study concludes that the developed instrument has strong construct validity and is suitable for measuring students’ interest in Arabic language learning. These findings provide an important empirical foundation for developing evidence-based educational measurement tools. Future research is recommended to conduct Confirmatory Factor Analysis (CFA) to validate the factor structure and to expand the application of this instrument to a more diverse population to enhance the generalizability of the results.